Roots of Forgiveness and Inner Peace: Exploring Gender and Geographical Identity among Muslim University Students - Nurlatifah, Andar Ifazatul; Ahman, Ahman; Yusuf, Syamsu; Ilfiandra, Ilfiandra (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
This study investigates the correlation between forgiveness and inner peace and examines differences based on gender and place of residence among emerging adult Muslim university students in Indonesia. A cross-sectional survey was conducted with 438 randomly selected students (90 males, 348 females) from 17 universities across Sumatra, Java, Kalimantan, and Sulawesi. Inner peace was measured using a 19-item validated scale (α = 0.764), while forgiveness was assessed with an adapted TRIM-18 (α = 0.723). Data analysis involved Spearman’s rho, Mann–Whitney U, Kruskal–Wallis, and Dunn tests. A significant positive correlation was found between forgiveness and inner peace (ρ = 0.326, p < 0.001). Gender differences were evident in several inner peace dimensions—Acceptance of Loss, Inner Balance and Calmness, and total Inner Peace—as well as in forgiveness, particularly in Avoidance Motivation and overall Forgiveness scores. Residence-based differences were also observed. Kruskal–Wallis tests showed significant group differences in Avoidance and Benevolence Motivation. Dunn’s post-hoc tests revealed that students from mountainous areas had significantly lower avoidance motivation than those from coastal regions, while highland residents showed higher benevolence motivation than lowland residents. These findings suggest that gender and geographic environment significantly influence students’ emotional and spiritual well-being. This study underscores the importance of promoting inner peace and forgiveness in higher education settings and provides valuable insights for educators and counselors to cultivate supportive campus environments that foster students’ holistic development. Penelitian ini bertujuan untuk mengkaji korelasi antara pemaafan dan kedamaian batin, serta mengeksplorasi perbedaan berdasarkan jenis kelamin dan tempat tinggal terhadap kedua konstruksi tersebut pada mahasiswa Muslim dewasa awal di Indonesia. Menggunakan survei potong lintang, data dikumpulkan dari 438 mahasiswa (90 laki-laki, 348 perempuan) yang dipilih secara acak dari 17 universitas di Sumatra, Jawa, Kalimantan, dan Sulawesi. Skala Kedamaian Batin terdiri dari 19 butir valid (α = 0,764), sementara pemaafan diukur menggunakan adaptasi TRIM-18 (18 butir, α = 0,723). Data dianalisis menggunakan Spearman’s rho, U Mann–Whitney, Kruskal–Wallis, dan uji Dunn. Terdapat korelasi signifikan antara kedamaian batin dan pemaafan (ρ = 0,326, p < 0,001). Perbedaan berdasarkan jenis kelamin muncul dalam kedamaian batin, khususnya pada aspek Penerimaan Kehilangan dan Keseimbangan serta Ketentraman Batin, total Kedamaian Batin, serta pada pemaafan, terutama pada aspek Pengurangan Motivasi Penghindaran, dan total Pemaafan. Perbedaan dalam dimensi pemaafan juga ditemukan berdasarkan tempat tinggal. Uji Kruskal–Wallis menunjukkan perbedaan signifikan dalam kelompok terhadap Pengurangan Motivasi Penghindaran dan Motivasi Kebaikan. Uji Dunn dengan koreksi Holm menunjukkan bahwa individu dari daerah pegunungan menunjukkan motivasi penghindaran yang secara signifikan lebih rendah dibandingkan mereka yang tinggal di daerah pesisir, sementara mereka yang tinggal di dataran tinggi menunjukkan Motivasi Kebaikan yang lebih tinggi dibandingkan mereka yang tinggal di dataran rendah. Dalam konteks pendidikan tinggi, penelitian ini menyoroti peran jenis kelamin dan lingkungan dalam membentuk perkembangan emosional dan spiritual mahasiswa. Temuan ini diharapkan dapat memberikan wawasan bagi pendidik dan konselor dalam membangun budaya kampus yang mendukung kedamaian batin dan pemaafan sebagai bagian dari kesejahteraan holistik mahasiswa.